Hubungan Usia, Paritas, Dan Ketuban Pecah Dini Dengan Kejadian Bayi Berat Lahir Rendah Di Ruang Bersalin Rumah Sakit Daerah Idaman Kota Banjarbaru Tahun 2024 - Faradiba Animurti; Rita Kirana; Nur Rohmah Prihatanti (Jurnal Kesehatan Indonesia, 2024)
The incidence of LBW in Banjarbaru city has increased from 5.6% in 2022 to 5.8% in 2023, and contributed to the highest neonate mortality rate in the last 2 years. The causes of LBW include age, parity and PROM in mothers who are at risk of increasing infection for the mother and fetus.To determine the relationship between maternal age, parity, and PROM with the incidence of LBW in the Delivery Room of Idaman Hospital, Banjarbaru City in 2024. This study used a cross-sectional approach with chi square test with total sampling technique as many as 339 maternal respondents. The dependent variable of this study was LBW, and the independent variables were age, parity and PROM. This research instrument used patient register. The results showed the incidence of LBW was 18%, age at risk was 24%, grandemultipara was 14%, and the incidence of PROM was 15%. The results of the chi-square test obtained maternal age (? = 0.593), parity (? = 0.191) did not have a significant correlation with the incidence of LBW and PROM (? = 0.005; OR = 2.552) had a correlation with the incidence of LBW.There are other factors that influence the incidence of LBW besides age and parity. Mothers with PROM have a 2.552 times greater risk of experiencing LBW.